Impact of patient nationality on the severity of early side effects after radiotherapy - Köksal, Mümtaz; Streppel, Romy; Hauser, Stefan; Abramian, Alina; Kaiser, Christina; Gonzalez-Carmona, Maria; Feldmann, Georg; Schäfer, Niklas; Koob, Sebastian; Banat, Mohammed; Hamed, Motaz; Giordano, Frank Anton; et al. (Journal of cancer research and clinical oncology, 2023)
Major demographical changes in Germany commenced in the 1960s. Ongoing humanitarian crises in the Ukraine with subsequent immigration will have also long-range effects on national provision of cancer treatment. Ensuring the best possible outcomes for each cancer patient undergoing radiotherapy requires the prediction and prevention of unfavorable side effects. Given that recent research has primarily focused on clinical outcome indicators solely, less is known regarding sociodemographic predictors of therapeutic outcomes, such as patient nationality. Here, we investigated whether the severity of early side effects after radiotherapy are associated with patient nationality and other sociodemographic and clinical characteristics.